Impacts of early insulin treatment vs glimepiride in diabetic patients with background metformin therapy: A nationwide retrospective cohort study. Issue 9 (5th March 2021) - Yen, Fu-Shun; Hsu, Chih-Cheng; Su, Yuan-Chih; Wei, James Cheng-Chung; Hwu, Chii-Min
Abstract : Abstract: Type 2 diabetes mellitus (T2DM) is a progressive disease. After metformin failure, the addition of insulin or sulfonylureas might increase the risk of hypoglycemia and cardiovascular (CV) morbidity. Here, the risk of all-cause mortality was compared between early insulin treatment and glimepiride use in T2DM patients with background metformin therapy. We conducted a 9-year retrospective cohort study from the population-based National Health Insurance Research Database in Taiwan. A total of 2054 patients with T2DM under insulin or glimepiride treatment were enrolled during 2004 to 2012. Overall event rates of all-cause mortality were compared between 1027 insulin users and 1027 matched glimepiride users. After the propensity score matching, the mortality rates were 72.5 and 4.42 per 1000 person-years for insulin users and glimepiride users. The adjusted hazard ratio of mortality was 14.47 (95% CI: 8.64–24.24; P value <.001) as insulin compared with glimepiride users. The insulin users had significantly higher risk of CV death (adjusted hazard ratio 7.95, 95% CI 1.65–38.3, P  = .01) and noncardiovascular death (adjusted hazard ratio 14.9, 95% CI 8.4–26.3, P  < .001). The nationwide study demonstrated that metformin plus insulin therapy was associated with higher risk of all-cause mortality.